The lower German limes = De Nedergermaanse Limes = Der Niedergermanische Limes - Graafstal, Erik P., (Frontiers of the Roman empire., 2022)
The frontiers of the Roman empire together form the largest surviving monument of one of the world's greatest states. They stretch for some 7,500 km through 20 countries which encircle the Mediterranean Sea. The remains of these frontiers have been studied by visitors and later by archaeologists for several centuries. Many of the inscriptions and sculpture, weapons, pottery and artefacts created and used by the soldiers and civilians who lived on the frontier can be seen in museums. Equally evocative of the lost might of Rome are the physical remains of the frontiers themselves. The aim of this title is not only to inform the interested visitor about the history of the frontiers but to act as a guidebook as well.